Event management system (EMS) - Mohd Yusani, Ayub (2015)
Event management system application (EMS) is an interesting way to bring full potential of a company. It can increase market potential, easier management of the company and reduce various costs for the company. EMS has proven a helpful system and a lot of company are start using it to manage their company. For Arul Supply Trading, this catering company are about to reveal its potential by this software. The owner of this company is wise enough to approve me to build event management system for the company. Hope that this software can increase its potential not only in Malaysia but include neighbor country like Indonesia or Singapore.